Editorial: Volume 9, Issue 1 - Kristy L Archuleta (Journal of Financial Therapy, 2018)
This year has been an exciting year for the Journal of Financial Therapy’s sponsoring organization, Financial Therapy Association. An idea was sparked many years ago by the FTA Board of Directors that a designation or credential should be created. With the ushering in of CFT-I™, it is a critical moment for further research to be conducted that will continue to help inform the practice of financial therapy. Now, more than ever, we must connect the areas of practice, research, and theory to not only inform best practices of financial therapy, but also to legitimize the work. Meaningful research to inform for the field cannot be conducted without collaboration with practitioners, and credible practice cannot be done be without theoretical and empirical support.
Keywords: editorial; financial therapy; research; certified financial therapist